Adapting Philippine agriculture to climate change - Rosegrant, Mark W.; Sombilla, Mercedita A.; Perez, Nicostrato D.; Pradesha, Angga; Thomas, Timothy S. (ISEAS – Yusof Ishak Institute, 2022)
This collection of essays provides a wealth of information and analysis about the Philippine economy and the role of agriculture and economic policy in it. The Philippine experience has been quite different from the highly successful Asian economies, with a long period of low growth until the turn of the century and only then greater success. The authors cover not only the Philippine experience but also place it in its Asian context and that of developing countries more generally. They report on the lessons learned, both positive and negative, from the various economic policies that have been adopted, with regard to both agriculture and to economic inequality. Those interested in Philippine economic development, and Asian development more broadly, will find this an important reference work